Individualized dosing of enoxaparin for subjects with renal impairment is superior to conventional dosing at achieving therapeutic concentrations - Barras, Michael A; Duffull, Stephen B; Atherton, John J; Green, Bruce (Therapeutic drug monitoring, 2010)
Enoxaparin is an anticoagulant used in the treatment of thromboembolic diseases. It is a hydrophilic molecule that is, predominantly, eliminated renally with few data to support dosing for subjects with renal impairment and/or obesity. A recently conducted randomized controlled clinical trial compared individualized enoxaparin doses based on lean body weight and renal function to conventional dosing. During this trial, anti-Xa concentrations were collected using a sparse sampling design and a population pharmacokinetic model was developed to describe the data. The current study evaluated the ability of the individualized dose to achieve and maintain anti-Xa concentrations within the therapeutic range (0.5-1.0 IU/mL) in subjects with renal impairment and/or obesity. A matched comparison of the two dosing strategies was undertaken using individual model predicted anti-Xa concentrations generated every 30 minutes to 120 hours post initiation of therapy. Concentration-time curves were generated for each subject and the proportion of time in the therapeutic, supratherapeutic, and subtherapeutic ranges were determined. When compared with conventional dosing, individualized dosing in subjects with renal impairment resulted in a significantly greater proportion of time in the therapeutic range (median [range] = 69.9% (11.3-91.8) versus 42.6% [13.9-71.4], P = 0.02) and a significantly reduced proportion of time in the supratherapeutic range (median [range] = 9.3% (0%-67.0%) versus 37.1% (0%-85.7%), P = 0.02). Although there was a trend toward a greater proportion of time in the therapeutic range in obese subjects, this did not achieve statistical significance. Individualized dosing in subjects with renal impairment is more effective than conventional dosing at achieving and maintaining therapeutic anti-Xa concentrations, which could decrease the risk of bleeding events and mortality in these subjects.